2010
DOI: 10.1128/ec.00198-10
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus fumigatus flbB Encodes Two Basic Leucine Zipper Domain (bZIP) Proteins Required for Proper Asexual Development and Gliotoxin Production

Abstract: The opportunistic human pathogen Aspergillus fumigatus reproduces asexually by forming a massive number of mitospores called conidia. In this study, we characterize the upstream developmental regulator A. fumigatus flbB (AfuflbB). Northern blotting and cDNA analyses reveal that AfuflbB produces two transcripts predicted to encode two basic leucine zipper domain (bZIP) polypeptides, AfuFlbB␤ (420 amino acids [aa]) and AfuFlbB␣ (390 aa). The deletion of AfuflbB results in delayed/reduced sporulation, precocious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 40 publications
(66 reference statements)
3
69
0
Order By: Relevance
“…In this model, upstream regulator AfuFluG is proposed to activate Afuflb (e.g. AfuflbB and AfuflbE; Yu et al, 2006;Kwon et al, 2010;Xiao et al, 2010;Yu, 2011) and AfuBrlA, thereby triggering the central regulatory pathway (AfubrlAAAfuabaAAAfuwetA) of conidiation. Subsequently, AfuvosA (Ni & Yu, 2007) is activated by AfuAbaA with the assistance of AfuWetA.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, upstream regulator AfuFluG is proposed to activate Afuflb (e.g. AfuflbB and AfuflbE; Yu et al, 2006;Kwon et al, 2010;Xiao et al, 2010;Yu, 2011) and AfuBrlA, thereby triggering the central regulatory pathway (AfubrlAAAfuabaAAAfuwetA) of conidiation. Subsequently, AfuvosA (Ni & Yu, 2007) is activated by AfuAbaA with the assistance of AfuWetA.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of recent studies, we characterized the functions of FlbE and FlbB in Afu [39, 40]. The predicted Afu FlbE protein is composed of 222 aa in length.…”
Section: Conserved Roles Of Brla-abaa-weta In Aspergillus Conidiationmentioning
confidence: 99%
“…Xiao et al [40] conducted a series of molecular analyses and found that AfuflbB produces two transcripts predicted to encode two b-zip polypeptides, Afu FlbBb (420 aa) and Afu FlbBa (390 aa). AfuflbB deletion results in delayed and reduced conidiation, precocious cell death, the absence of conidiophore development in liquid submerged culture, altered expression of AfubrlA and AfuabaA , and the lack (or a reduction) in gliotoxin production.…”
Section: Conserved Roles Of Brla-abaa-weta In Aspergillus Conidiationmentioning
confidence: 99%
“…To date a number of key asexual developmental regulators such as AbaA, BrlA, WetA, and Velvets have been identified and characterized in A. fumigatus [6,13,15,27]. AbaA plays a crucial role in the differentiation of phialides, the conidiogenous cells, which are required for formation of conidiospores.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, brlA mRNA is clearly detectable during a certain period of vegetative growth (~18~24 h) [6,13,15]. Moreover, the absence of abaA causes delayed autolysis and cell death, whereas the overexpression of abaA accelerates these processes [13].…”
Section: Introductionmentioning
confidence: 97%